Nanoparticle formulation of ethanolic extract of Syzygium polyanthum leaf using chitosan and cross-linking method - Hidayati, Evi Nurul; Rahayyu, Annisa Maulidia; Masruriati, Eni (Universitas Ahmad Dahlan, 2025)
Syzygium polyanthum (bay leaves) is widely used in Indonesia and has been shown to have pharmacological activity, such as antihyperlipidemia. The nanoparticle is a delivery system that enhances therapy effectiveness, minimizes side effects, and ensures safety. Therefore, this study aimed to improve the antihyperlipidemic efficacy of Syzygium polyanthum extract by formulating it into nanoparticles. The polymer that is used in this nanoparticle formulation is chitosan, while the cross-linking agent that is used is sodium tripolyphosphate. Three formulations have been developed, each with different stirring times after crosslinking: F1 (20 minutes), F2 (90 minutes), and F3 (150 minutes). At the same time, nanoparticles produced were examined for particle size, ζ potential, polydispersity index, entrapment efficiency, and release study. Syzygium polyanthum extract is abundant in secondary metabolites, including alkaloids, flavonoids, saponins, triterpenoids, tannins, and quinones. The particle size data for F1, F2, and F3 were 257±6.68 nm, 232±2.54 nm, and 303±1.3 nm respectively, while the polydispersity index ranged from 0.242 to 0.383. The entrapment efficiency represented by quercetin, used to assess the extracted content of the nanoparticles, yielded results between 39.59% and 67.48%. A release study of nanoparticle Syzygium polyanthum (nanoparticle SP) showed that the extract represented by quercetin can be released from the system is 64-82% in 120 min. The ζ potential measurement in F2 indicated a value of 30.9±0.416 mV, suggesting that the nanoparticle SP formed possesses excellent stability. Among the formulas studied, F2 emerged as the most promising due to its combination of factors such as the smallest size, favorable polydispersity index, high entrapment efficiency, and desirable release profile values. All of the formula has the potential to provide a good therapeutic effect, such as antihyperlipidemia but it needs to be proven by further studies.